ANALISIS PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL DALAM MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA - Cindy Sitanggang; Meylin Simalango; Restina Purba; Dimas Fahruzi (CV. ADIBA AISHA AMIRA, 2024)
This study aims to see the influence of audiovisual learning media in increasing students' interest and motivation to learn. Learning that tends to be monotonous makes students have no interest and motivation in learning. Audiovisual learning media is expected to be able to provide a solution to this problem in the form of presenting more interesting and interactive information so that it can encourage more active student involvement. Audiovisual learning media utilizes audio and visual media simultaneously in presenting interesting learning materials interactively. This study uses a literature study method, by collecting information from previous studies, and analyzing sources of information from various books and articles that are analyzed descriptively. Several studies have shown that learning that utilizes audiovisual media can increase student involvement in understanding learning materials. Audiovisual media has been proven to increase student learning motivation both intrinsically and extrinsically. Audiovisual learning media requires technology and teacher skills in integrating effectiveness into the learning process.